Behaviour of dispersion indices in pattern detection of a population of angico, Anadenanthera peregrina (Leguminosae) - Malhado,A. C. M. (2004)
In this paper we calculate the values of eight pattern detection indices, using different quadrat sizes where individuals of angico above 1.5 m were located, in order to examine their statistical behaviour with increasing sample size. It was concluded that the best index is the standardized Morisita index (Ip) which is completely independent of sample size.